2017
DOI: 10.1055/s-0043-102946
|View full text |Cite
|
Sign up to set email alerts
|

Stellenwert der selektiven Lasertrabekuloplastik (SLT)

Abstract: Worldwide, in recent years, selective laser trabeculoplasty (SLT) has developed into a very successful therapy for glaucoma. The article provides a review of the literature from PubMed and clinical experience. SLT is equally efficacious to argon laser trabeculoplasty (ALT) and to a first-line glaucoma medication. SLT can be used in most common forms of open-angle glaucoma and ocular hypertension. In contrast to ALT, SLT is repeatable and requires much less energy. SLT has been reported to be also successful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Selective laser trabeculoplasty (SLT), used since 1998 when the first successful protocol was described, has become an established method for lowering the intraocular pressure (IOP) in the treatment of open-angle glaucoma (OAG) and ocular hypertension (OH) [1][2][3][4][5]. Multiple prospective or retrospective studies clear demonstrated the safety and efficacy of SLT in reducing the IOP in eyes with OAG or OH [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser trabeculoplasty (SLT), used since 1998 when the first successful protocol was described, has become an established method for lowering the intraocular pressure (IOP) in the treatment of open-angle glaucoma (OAG) and ocular hypertension (OH) [1][2][3][4][5]. Multiple prospective or retrospective studies clear demonstrated the safety and efficacy of SLT in reducing the IOP in eyes with OAG or OH [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser trabeculoplasty (SLT) and argon laser trabeculoplasty (ALT) have similar efficacy and safety profiles (McAlinden ). Recently, SLT has been the focus of considerable research due to its potential as a first‐line treatment (Schlote ). A meta‐analysis of the effect of SLT in terms of IOP control has found that, in most trials, 360‐degree SLT was comparable to medication and that there was no significant difference between 360‐ and 180‐degree SLT (McAlinden ).…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[7][8][9] Since 1998, when the first successful protocol of selective laser trabeculoplasty (SLT) was described, a 532-nm Q-switched frequency doubled Nd:YAG laser with a single pulse of short duration and low influence (energy/area) is used and has become an established method for lowering the IOP in the treatment of OAG and ocular hypertension (OH). [10][11][12][13][14] Multiple prospective or retrospective studies clearly demonstrated the safety and effectiveness of SLT in reducing the IOP in eyes with medically uncontrolled OAG, where SLT was used as adjunctive treatment option. [15][16][17][18][19][20][21][22][23][24][25] Some prospective studies investigated the effectiveness of SLT in reducing the IOP as initial treatment in OAG, most of them compared initial SLT with medical monotherapy with prostaglandin analogues (PGA).…”
Section: Introductionmentioning
confidence: 99%